THE ANALYSIS OF ORGANIZATIONAL PLANT EXPORT PROCEDURES AT PT. CIHIDEUNG FLORA ARCHIPELAGO - Ludiya, Eka; Fadila Rahma Berliana (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study discusses the analysisof the ornamental plant export procedures carried out by PT.Cihideung Flora Nusantara. The focus of this research is on the export procedures for ornamental plants,with the aim of understanding the stage and steps taken by one ornamental plants exporting company in conducting exportactivities. The methode employed in this research is descriptive analysis, which depicts the procedures established by the company in carrying out export activities. The findings indicate that there is no specific procedure developed by the company to address damage occurring during export activities,particularly in the shipping process. Additionally, due to the company’s human resource limitations, there is an overlap in the job responsibilities of the workers. The author suggest a solution, emphasizing the need for introduction of the new procedures in the company, especially when customers report damages. Moreover, the addition of more staff is recommended to alleviate the workload and prevent overlapping job responsibilities among employees.